2022
DOI: 10.3390/antibiotics11020199
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence Survey of Antibiotic Use across 13 Hospitals in Uganda

Abstract: Standardized monitoring of antibiotic use underpins the effective implementation of antimicrobial stewardship interventions in combatting antimicrobial resistance (AMR). To date, few studies have assessed antibiotic use in hospitals in Uganda to identify gaps that require intervention. This study applied the World Health Organization’s standardized point prevalence survey methodology to assess antibiotic use in 13 public and private not-for-profit hospitals across the country. Data for 1077 patients and 1387 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 56 publications
11
50
0
Order By: Relevance
“…The prevalence of antibiotic use in the present study was high. Our findings are in line with a study that was conducted in Iraq though a higher prevalence (93.7%) was reported [57], 88.2% in Eswatini [58], slightly lower prevalence (82.3%) in Pakistan [35], 74% in Uganda [59], and 60.6% in Ethiopia [60]. These findings are higher than the reference value of less than 30% recommended by the WHO [31] [32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of antibiotic use in the present study was high. Our findings are in line with a study that was conducted in Iraq though a higher prevalence (93.7%) was reported [57], 88.2% in Eswatini [58], slightly lower prevalence (82.3%) in Pakistan [35], 74% in Uganda [59], and 60.6% in Ethiopia [60]. These findings are higher than the reference value of less than 30% recommended by the WHO [31] [32].…”
Section: Discussionsupporting
confidence: 91%
“…Ghana [28], and Uganda [59]. On the contrary, In China, a study revealed that most antibiotics consumed in healthcare facilities belonged to the Watch group [67].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that most prescribed antibiotics belonged to the Access group. These ndings corroborate reports from a point prevalence survey across six hospitals in Tanzania that revealed that most patients received antibiotics from the Access group [61], similar to what was reported in Eswatini [53], Ghana [26], and Uganda [54]. On the contrary, In China, a study revealed that most antibiotics consumed in healthcare facilities belonged to the Watch group [62].…”
Section: Discussionsupporting
confidence: 88%
“…Similar ndings were reported in other surveys where the overall compliance with the outlined prescribing guidelines was suboptimal [52,64,65]. Lower adherence to treatment guidelines was reported in Uganda [54]. Non-adherence to the standard treatment guidelines of infectious diseases may be due to the absence of these guidelines in healthcare facilities [33,54], out of stock of key antibiotics [55], prescriber preferences, lack of e cient laboratory services and lack of proper diagnostic stewardship [54].…”
Section: Discussionsupporting
confidence: 57%
“…Non-prescribed antibiotics are known to increase inappropriate of antibiotics and increase global use and misuse (34), with the highest non-prescription use found in LMICs, at between 19-100% in some cases (35). Coupled with poor adherence to treatment guidelines in Uganda (17), this practice compounds access to unauthorized parallel markets for antibiotics (36), making AMU surveillance more problematic. Uganda has recently assessed policies and regulations on antibiotic stewardship -a key WHO Benchmark activity, with the activity ongoing in Tanzania.…”
Section: Strengthen the Implementation Of Policies And Regulations On...mentioning
confidence: 99%